Antibacterial Effect of Mastic Gum on Aerobic Oral Bacteria - AL – Mofarji, talib; AL- Zahid, Nahidha; Al –hashimy, esra (Iraqi National Journal of Nursing Specialties, 2013)
Objective: To evaluate the antibacterial effect of mastic gum against the most common aerobic oral bacteria and emphasized on oral streptococci. Methodology: In this study 10 persons (males and females of 18-60 years old) were randomly assigned to chew mastic gum (1.5 gm for 45 minutes). Mouth washes were collected before and after gum chewing .The two mouth washes were diluted (10-1 – 10-6) and cultivated aerobically for 24 hours at 37C0 on BHI agar for total bacterial count and on MSF agar for counting the oral streptococci. Results: The results showed that the total bacterial count for staphylococci, Neisseria and oral streptococci on BHI agar and MSF agar for oral streptococci after mastic chewing were highly reduced and arrived to more than 5 grades according to statistical analysis. Recommendations: To keep your mouth healthy we recommended the followings : Chewing of mastic gum daily , using oral mastic products such as toothpaste and mouthwash, and incorporation of mastic as powder with some type of foods.